An identity-based approch to communication - Sa Sequeira, Arminda (2012)
The main objective of this paper is to evaluate the key elements in the construction of cosistent organisational messages over time. In order to accomplish that, we propose the aligment of several elements: vision, misson, objectives, cultural values, optimal identity attributes, positioning, type of messages, communication style and means, and image...